Physical profiles and dietary practices of semi-professional and collegiate male rugby union players in Malaysia - Norsyazmi Mohd
It has been advocated that physical profiles and proper nutrition play an important role in professional rugby players; however, only a limited number of research have investigated the physical demands and dietary intake of lower-level rugby players.The aim of the first study (Chapter 3) was to determine the anthropometric and physical fitness characteristics of semi-professional and collegiate rugby union players. Ninety-four rugby players from seven different rugby clubs (43 collegiate and 51 semi-professional) were categorised according to their positions and playing levels and measured for total weight, height, and body composition. Differences between playing levels and positions were consistent with previous studies, with semi-professional players tending to be taller, heavier, more aerobically fit, and have lower explosive power than collegiat players. Within semiprofessional players, the vertical jump test (VJT) was the only variable to have a strong correlation effect with body fat percentage (BF%) (r = -0.718), indicating players of higher playing levels may be selected due to other key indicators. In collegiate players, BF% demonstrates strong correlation effect with 3-sec sprint test (r = 0.988), agility (r = 0.612), YJT (r = -0.808) and aerobic fitness (r = -0.943). Having uccessfully determined the anthropometric and physical fitness characteristics of semi-professional and collegiate rugby players, the second study (Chapter 4) aimed to assess the players' somatotypes and body shapes using the Heath-Carter method and 3D body scanning technology. The whole mean somatotype was 4.7-7.5-1.0 (1.6-1.5-1.2) in semi-professional and 3.5-6.5-1.5 (1.3- 3.4-0.8) in collegiate players. Semi-professional players were more mesomorphic (p = 0.01), more endomorphic (p < 0.001), and less ectomorphic (p = 0.02) than collegiate players. K-mean analysis of the 3D measurements revealed that semi-professional and collegiate players could be grouped into three clusters. The cluster centroids of clusters 1 to 3 of semi-professional and clusters 1 and 2 of collegiate resembled closely to being endo-mesomorphic . The cluster centroid of cluster 3 of collegiate players resembles being ecto-mesomorphic. By using the anthropometric measurements associated with each cluster, players can be differentiated based on their playing positions. The third study (Chapter 5) aimed to assess the energy expenditure and dietary intake of fifty-two (30 collegiate and 22 semi-professional) players recruited from four clubs during the pre-, inseason, and match day. The findings of this study demonstrate that playing positions and levels has no effects on dietary intake. Moreover, semi-professional and collegiate players were in constant energy deficit throughout the pre- and in- season, with inadequate carbohydrate intake compared to the current recommendations. Match day nutritional practices revealed that both groups are not fulfilling the energy intake needed to sustain throughout the 80min game. It is possible that these results were influenced by severe under-reporting. To conclude, there are clear differences in terms of the physical profiles between semi-professional and collegiate rugby players. Both group of players are in energy and macronutrient deficit compared to the current recommendations. A practical application of these data is to form the basis for a future development program for players of lower playing levels by designing a more systematic and specific training program along with a valid nutritional strategy.